Peasant Cooperation and Agricultural Growth in Historical Perspective: Southeastern Shanxi in the 1950s. (September 2019) - Gao, Yuan
Historical evidence suggests that peasant cooperation in the form of mutual aid teams and co-ops contributed to agricultural growth in southeastern Shanxi before 1958. Well-managed mutual aid teams and co-ops could improve the efficiency of input allocation, help to increase the use of traditional inputs, and accelerate the diffusion of output-enhancing technologies. The case of the Guo Yu'en co-op in Chuandi village illustrates how institutions providing sufficient work incentives could emerge in rural communities. By linking the southeastern Shanxi story to national trends of agrarian change in the 1950s, this article emphasizes that cooperativization before the Great Leap Forward generated heterogeneous effects across different regions and cannot be indiscriminately labeled as inefficient.